Quaternary Glaciation of the Great Lakes Region: Process, Landforms, Sediments, and ChronologyMinimum age of the Mapleton, Tully, and Labrador Hollow moraines indicates correlation with the Port Huron Phase in central New York State - Kehew, Alan E.; Curry, B. Brandon; Kozlowski, Andrew L.; Bird, Brian C.; Lowell, Thomas V.; Smith, Colby A.; Feranec, Robert S.; Graham, Brandon Lars (Geological Society of America, 2018)
The glaciated terrain along the northern edge of the Appalachian Plateau in the eastern Finger Lakes of central New York has long been recognized as an important location for meltwater routing and for proglacial lake development in the Great Lakes region. Despite recognition of multiple ice margins formed by the Ontario Lobe of the Laurentide ice sheet during the late Wisconsinan, numerical age control of several margins has been elusive, particularly in regard to regional readvances of the Port Bruce (ca. 16,980–18,000 cal [calibrated] yr B.P.) and Port Huron (ca. 14,300– 16,000 cal yr B.P.) Phases. Utilizing light detection and ranging (LiDAR) terrain models in the eastern Finger Lakes area, we identified and described the Mapleton, Tully, and Labrador Hollow moraines. Associated ice-marginal landforms include push moraines, fans, and hummocky topography. In places, these features intrude into the northern heads of through valleys. Coring of three basins directly associated with these landforms yielded more than 20 samples of boreal tree needles and twigs, and Dryas leaves. Accelerated mass spectrometry (AMS) radiocarbon assay results indicate that poststadial lacustrine sedimentation began at ca. 15,000 cal yr B.P., consistent with ages of the Port Huron Phase.

NEW AMS RADIOCARBON DATES FROM LATE PLEISTOCENE MASTODONS AND MAMMOTHS IN NEW YORK STATE, USA - Feranec, Robert S.; Kozlowski, Andrew L. (RADIOCARBON, 2012)